A New Complex Borohydride LiAl(BH4)2Cl2 - Oleksandr Dolotko; Takeshi Kobayashi; Ihor Z. Hlova; Shalabh Gupta; Vitalij K. Pecharsky (Inorganics, 2021)
A new mixed alkali metal–aluminum borohydride LiAl(BH4)2Cl2 has been prepared via mechanochemical synthesis from the 2LiBH4–AlCl3 mixture. Structural characterization, performed using a combination of X-ray powder diffraction and solid-state NMR methods, indicates that the LiAl(BH4)2Cl2 phase adopts a unique 3D framework and crystallizes in an orthorhombic structure with the space group C2221, a = 11.6709(6) Å, b = 8.4718(4) Å, c = 7.5114(3) Å. The material shows excellent dehydrogenation characteristics, where hydrogen evolution starts at Tons = 70 °C, releasing approximately 2 wt.% of nearly pure (99.8 vol.%) hydrogen and a very small amount (~0.2 vol.%) of diborane. When compared to halide-free mixed alkali metal–aluminum borohydrides, the presence of Al‒Cl bonding in the LiAl(BH4)2Cl2 structure likely prevents the formation of Al(BH4)3 upon decomposition, thus suppressing the formation of diborane.